Faculty of medicine open day - Abdul Aziz, Mardiana; Mohd Nasir, Nadzimah; Razali, Ruzi Hamimi; Mahamooth, Mas Irfan Jaya; Haron, Muhammad Huzaimi (Faculty of Medicine, 2022)
On 23rd November 2022, the Faculty of Medicine (FoM), UiTM held its first Open Day as part of a series of events to celebrate the faculty’s 20th anniversary. The Open Day was held in UiTM Sg Buloh Campus and was attended by participants from Pusat Asasi UiTM, secondary school students from several boarding schools in Malaysia, as well as the faculty’s medical students and staff.